Fluorination with Xenon Difluoride : Part X: Reactivity of Hexamethylbenzene - M. Zupan (CHIMIA)
Fluorination of hexamethylbenzene with xenon difluoride catalyzed by hydrogen fluoride resulted in pentamethylbenzyl fluoride, while fluorination in the presence of trifluoroacetic acid resulted in pentamethylbenzyl trifluoroacetate.